Watts in the poles - What does it take to be a cross-country skier? A meta-analysis of the Swedish Ski Federation`s performance profile - Kuylenstierna, D. (Skisens, 2025)
There are still not many of the world`s cross-country skiers who train and compete daily with a power meter, but slowly an awareness is beginning to spread. This is evidenced, among others, by Edvin Anger, and even Jens Burman has taken notice of it during cycling sessions. At Skisens, we`re very pleased to see this growing awareness about watts, since understanding a metric is the first step to being able to use it. As a user, the most important knowledge is not primarily how it is measured, but how to interpret the result. Step one is understanding what constitutes a good number and what is a less competitive number in relation to one`s own ambitions. In parallel with developing the measurement tools, we at Skisens are therefore working extensively to build this knowledge base.